Timing of Strobilurin Fungicide for Control of Top Dieback in Corn - Eric Adee; Stu Duncan (Kansas Agricultural Experiment Station Research Reports, 2017)
Significant yield losses can result from top dieback (TDB) in dent corn, which is caused by infection by the fungus,Colletotrichum graminicola, causing anthracnose. Research is limited on the effectiveness of fungicide application because of the unpredictable nature of the disease. Three field studies were established to assess the timing of fungicide application on foliar diseases that developed TDB, one in Illinois (2010) and the other two in Kansas (2015 and 2016). Fungicide applications at tasseling and later were effective in reducing the incidence of TDB by greater than 20% and increasing yield greater than 14 bu/a, or greater than 7%, while earlier applications (V5 to V8) did not reduce TDB or increase yield compared to the untreated check.
Keywords: top dieback; corn; fungicide; anthracnose; strobilurin